Analytical solutions for thermo-mechanical soil structure interaction in energy piles - Cossel, Aaron (Kansas State University, 2019)
While traditional pile foundations have been used for many years to transfer loads from superstructures to the subsurface, energy piles became especially popular in the last 15 years. Energy piles are thermo-active foundations that enable transfer of thermal energy between the subsurface and the superstructure. They rely on the use of ground source heat, which is economically efficient, environmentally friendly, and sustainable way to heat and cool large structures. Unlike air, the temperature of the soil remains relatively constant throughout the year below the certain depth that depends on the climatic zone. To extract the thermal energy from the ground geothermal loops are embedded into energy piles. The main purpose of such thermo-active foundation systems is to transfer deep ground heat into a building during the winter and out of the building during the summer through fluid circulating within the geothermal loop. These thermo-active foundations may need to be supplemented with air based heating/cooling systems. This study investigates thermo-mechanical response of end bearing and semi floating energy piles through use of mathematical modeling. To this end, it is assumed that the energy pile behaves as thermo-elastic material while the soil-pile interface remains in the elastic state. These assumptions have been used and verified in several other studies. The analytical solutions for axial displacement, strain, and stress have been found for a single layered and multi layered soils underlain by the bedrock. Furthermore, the analytical solutions for mechanical and thermal loads have been validated against the full scale in situ tests. It is found that in case of net heating the end bearing pile model gives better predictions than the semi floating pile model and in the case of a combined thermal and mechanical semi floating pile model is better. The analytical solutions developed herein provide in depth qualitative understanding of the load transfer mechanism in energy piles as well as quick, simple, and elegant computation of displacement, stress, and strain.
Keywords: Soil structure interaction; Energy pile; Thermo-mechanical; End bearing; Semi-floating